Optimasi Biaya Distribusi Air Minum Galon Menggunakan Model Transportasi NWC, Least Cost, dan VAM - Ernawati Ernawati; Intan N. C; Aldi A; Abby Yazid Bustommy (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
Distribution is an essential component of the supply chain that directly affects a company's operational costs. This study examines the distribution of bottled drinking water from three distributors, namely Agung Berkah (Sukamulya), Mr. Watter (Cikupa), and Herman Depot (Citra Raya), to three destination areas: Balaraja, Telagasari, and Tigaraksa. The current distribution process is based on experience, making it unclear whether transportation costs have been minimized. Therefore, this study aims to determine the most efficient distribution pattern by comparing three transportation model methods: the Northwest Corner (NWC), Least Cost (LC), and Vogel's Approximation Method (VAM). The research employed a quantitative approach using data on transportation capacity, regional demand, and delivery costs per trip calculated based on fuel consumption. The results show that the NWC and LC methods produce the same total distribution cost of IDR 2,250,000 per month, whereas the VAM method yields the lowest total cost of IDR 2,230,000 per month, resulting in a cost saving of IDR 20,000 compared with the other two methods. This cost reduction is achieved because the VAM method considers penalty values (opportunity losses) before allocating shipments, producing an initial solution that is closer to the optimal solution. The findings suggest that Telagasari should be supplied by Mr. Watter, while Balaraja and Tigaraksa should be supplied by Agung Berkah. Herman Depot should serve as a backup distribution center due to its relatively higher transportation cost. Future studies are recommended to apply the Modified Distribution (MODI) method to verify that the obtained solution is truly optimal.